Tonic and Phasic Alertness Training: A Novel Behavioral Therapy to Improve Spatial and Non-Spatial Attention in Patients with Hemispatial Neglect - DeGutis, Joseph M.; Van Vleet, Tom (Frontiers in Human Neuroscience, 2010)
Hemispatial neglect is a debilitating disorder marked by a constellation of spatial and non-spatial attention deficits. Patients’ alertness deficits have shown to interact with lateralized attention processes and correspondingly, improving tonic/general alertness as well as phasic/moment-to-moment alertness has shown to ameliorate spatial bias. However, improvements are often short-lived and inconsistent across tasks and patients. In an attempt to more effectively activate alertness mechanisms by exercising both tonic and phasic alertness, we employed a novel version of a continuous performance task (tonic and phasic alertness training, TAPAT). Using an AB design and employing sensitive outcome measures of spatial and non-spatial attention, we compared the effects of 9 days of TAPAT (36 min/day) in a group of patients with chronic neglect (N=12) with a control group of chronic neglect patients (N=12) who simply waited during the same training period. Compared to the control group, the group trained on TAPAT significantly improved on both spatial and non-spatial measures of attention with many patients failing to exhibit a lateralized attention bias at the end of training. TAPAT was effective for patients with a range of behavioral profiles and lesions, suggesting that its effectiveness may rely on distributed or lower-level attention mechanisms that are largely intact in patients with neglect. In a follow-up experiment, to determine if TAPAT is more effective in improving spatial attention than an active treatment that directly trains spatial attention, we trained three chronic neglect patients on either TAPAT or search training. In all three patients, TAPAT training was more effective in improving spatial attention than search training suggesting that, in chronic neglect, training alertness is a more effective treatment approach than directly training spatial attention.